Intertrial auditory neural stability supports beat synchronization in preschoolers. (February 2016) - Woodruff Carr, Kali; Tierney, Adam; White-Schwoch, Travis; Kraus, Nina
Highlights: The ability to synchronize to a beat is linked to language and literacy skills. We examine links between preschool synchronization and auditory neural encoding. We reveal a systematic relationship between synchronization and speech encoding. Synchronization provides an index of auditory neural precision in early childhood. Abstract: The ability to synchronize motor movements along with an auditory beat places stringent demands on the temporal processing and sensorimotor integration capabilities of the nervous system. Links between millisecond-level precision of auditory processing and the consistency of sensorimotor beat synchronization implicate fine auditory neural timing as a mechanism for forming stable internal representations of, and behavioral reactions to, sound. Here, for the first time, we demonstrate a systematic relationship between consistency of beat synchronization and trial-by-trial stability of subcortical speech processing in preschoolers (ages 3 and 4 years old). We conclude that beat synchronization might provide a useful window into millisecond-level neural precision for encoding sound in early childhood, when speech processing is especially important for language acquisition and development.